EFEKTIVITAS KARTU TANI DALAM DISTRIBUSI PUPUK BERSUBSIDI DI KECAMATAN NGRAMPAL KABUPATEN SRAGEN - Febriana, Fika; Maharani, Artita Devi; Mawardi, Nanang Kusuma (Fakultas Pertanian UST, 2023)
The study aims to determine the effectiveness of the farmer cards in the purpose of the distribution of subsidized fertilizers in Ngrampal District Sragen Regency and to determine the differences in the effectivenees of the distribution of subsidized fertilizer with farmer cards and without using farmer cards. The sampling technique in this study wa a simple random sampling technique. The method of determining the number of samples uses is the theory of Gay and Diehl, which is 10% of the total population, because the research conducted is distributive one.Data collection techniques use are questionnaires, interviews, documentation, and observation. The research was conductedat the Konco Tani Fertilizer Kiosk and the Sri Murni Fertilizer Kiosk. The result showed that the distribution of subsidized fertilizer using the farmers cards based on six appropriate indicators was quite effective. The distribution of subsidized fertilizers based on the right time, right price, right quality, and right place is classifieds very effective. The results showed that the effectiveness of using farmer cards in the distribution of subsidized fertilizers in Ngrampal District, Sragen Regency was still low because farmers did not understand how to distrubute subsidized fertilizers with farmers card because of the lack of conseling and socialization from the government regarding the use of farmer card . The experiment there were differences in the effectiveness of fertilizer distribution subsidized before and after using farmers card by 2.29%.